1995
DOI: 10.1083/jcb.131.6.1635
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom gene organization: structural arrangements of specific pre-mRNA transcription and splicing with SC-35 domains.

Abstract: Abstract. This work demonstrates a highly nonrandom distribution of specific genes relative to nuclear domains enriched in splicing factors and poly(A) ÷ RNA, and provides evidence for the direct involvement of these in pre-mRNA metabolism. As investigated in hundreds of diploid fibroblasts, human collagen Ietl and 13-actin DNA/RNA showed a very high degree of spatial association with SC-35 domains, whereas three nontranscribed genes, myosin heavy chain, neurotensin, and albumin, showed no such preferential as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
291
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(324 citation statements)
references
References 77 publications
26
291
3
Order By: Relevance
“…The genes are found outside of the XIST RNA (yellow), which extends beyond the Barr body, the visible manifestation of the heterochromatin. 49,50,58,59) and splicing and transcription factors localize (22,49,51,60,61). The act of silencing and condensing the inner core of Xi may make the existing concentration of protein-coding genes in the peripheral region more pronounced and observable.…”
Section: Discussionmentioning
confidence: 99%
“…The genes are found outside of the XIST RNA (yellow), which extends beyond the Barr body, the visible manifestation of the heterochromatin. 49,50,58,59) and splicing and transcription factors localize (22,49,51,60,61). The act of silencing and condensing the inner core of Xi may make the existing concentration of protein-coding genes in the peripheral region more pronounced and observable.…”
Section: Discussionmentioning
confidence: 99%
“…This RNA movement persists in transcriptionally inhibited cells. The movement of endogenous pre-mRNA to the speckles has been demonstrated in both transcriptionally active and silenced cells (Xing et al, 1995;Dirks et al, 1997;Ishov et al, 1997;Smith et al, 1999;Snaar et al, 1999;Johnson et al, 2000;Melčák et al, 2000). In addition, it has been shown that microinjected intron-containing RNA is within the cell nucleus processed into functional mRNA (Graessmann and Graessmann, 1982) and that several microinjected RNAs transcribed by RNA polymerase II and III localized at specific nuclear sites at which their corresponding endogenous counterparts were present in the steady-state distribution as shown by in situ hybridization (Jacobson et al, 1995(Jacobson et al, , 1997 Jacobson and Pederson, 1998a,b;Pederson, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Primary transcripts of certain genes as well as the spliced RNAs are mapped at sites of active transcription and outside of speckles (Zhang et al, 1994;Smith et al, 1999). On the other hand, pre-mRNAs from some other genes are shown to be associated with nuclear speckles (Xing et al, 1993(Xing et al, , 1995Huang and Spector, 1996;Ishov et al, 1997;Smith et al, 1999;Snaar et al, 1999;Johnson et al, 2000;Melčák et al, 2000). It thus remains unclear as to whether the nuclear speckles reflect localized accumulations of active splicing factors and whether the nucleus is compartmentalized with respect to splicing.…”
mentioning
confidence: 99%
“…HeLa cells were preextracted in cytoskeletal buffer (CSK: 100 mM NaCl, 300 mM sucrose, 3 mM MgCl 2, 10 mM Pipes at pH 6.8) containing 0.5% Triton-X 100 for 5 min on ice and fixed with 3.7% freshly prepared formaldehyde for 15 min at room temperature. The cells were washed in 1× PBS (pH 7.2) and heat denatured in 70% formamide and 2× SSC at 72°C for 5 min followed by hybridization with labeled chromosome 9-specific satellite probe (Q-biogene) in 2× SSC, 50% formamide, 10% dextran sulfate, yeast tRNA, and Cot-1 DNA overnight at 37°C as previously described (63).…”
Section: Methodsmentioning
confidence: 99%